(untitled) (Altre Modernità, 2011)
This essay constitutes a preliminary effort to explain the state fantasy with which Barack Obama hegemonized an alternative to the biopolitical settlement normalizing George W. Bush’s Global War on Terror (Pease 2009). In what follows, I intend to argue that Obama has not utterly displaced Bush’s Homeland State of Exception but that Obama’s governmentality presupposes it as the structuring logic through which he transformed the US state’s relationship with domestic and planetary peoples. I will be interested in particular in the role that Obama’s complex negotiation with the congeries of racial fantasies that he found condensed in the figure and the film Black Orpheus played in Barack Obama’s governmentality.